Punk ideals, school leaders and fashioning an "authentic" self. Issue 1 (May 2023) - Heffernan, Amanda; Thomson, Pat
The field of education is in dire need of different ways of thinking about attracting, supporting, and retaining school leaders. We see the idea of punk as a space that may offer some leeway for thinking differently about professionalism for school leaders. In this paper, we draw on thinking about punk subcultures to recognise the ways in which leaders hold self-expression and identity as important, while also thinking about how leaders as a collective might push back against some of the narrow ideas of who or what a school leader can be and do. We present findings from a mixed-methods study of women school leaders from around the world. Drawing on an anonymous survey and interviews, and literatures from sociology, fashion studies, and cultural studies, we explore women's experiences and identities as school leaders. The paper contributes to our understanding of professionalism and identity and also how we can better attract, support, and retain school leaders.